Legal Protection of The Rights of The Child Conflict with The Law in Criminal System in Indonesia - Titin Prialianti (Jurnal Daulat Hukum, 2018)
Kids are the future generation, since the past becomes a fact not in dispute. However, children and life does not always experience the world like a child's journey. Child and his life is a hope and a future generation that will bring Indonesia into a more dignified nation, because from an early age the child is equipped with moral education, religious, and cultural attitudes Indonesia known friendly and have a high tolerance. But in reality the child's life is not always straight and provide the ultimate comfort of the child's world. The fact is not little children who should have cute and adorable behavior actually stuck on adult human life is not worth living children. Children who entered into a legal conflict issues requires more attention to find a way out, a solution and not reckless handling so as not to negatively impact children. Revision to Act No. 3 of 1997 on Juvenile Justice into Act No. 11 of 2012, concerning child Criminal Court System, provides a decent enough room for children coming into conflict of laws. Quite feasible because in the Act No. 11 of 2012 which contains 108 Article, more humane in the treatment of children coming into conflict of laws.                Keywords: Legal Protection, Rights of the Child in conflict.